Tinjauan Literatur Naratif: Inovasi dalam Manajemen Nyeri Postoperatif Berbasis Digital - Nurul Imam; Pradita Ayu Fernanda; Khalifatus Zuhriyah Alfianti; Eka Mei Dianita; Ni Putu Diah Ayu Rusmeni (KHD Production, 2024)
Effective postoperative pain management is a key element in patient recovery after surgery, but often standard protocols do not take advantage of the potential of real-time data and digital technology for more responsive therapy adjustments. The aim of this study was to identify the latest innovations in digital-based postoperative pain management. A literature review examined the use of digital technology in postoperative pain management, focusing on smartphone apps, wearable devices, and real-time data analytics for monitoring patient pain with the keywords